LAYANAN BIMBINGAN DAN KONSELING ANAK DI TK KEMALA BHAYANGKARI 13 PONTIANAK KOTA - Azzahra, Nurma Annisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Guidance and counseling services for children as the help given to children in developing optimal developmental aspects. The goal is making the children to be responsible and independent individuals in resolving their problems. The research question was how the form of planning, implementation, evaluation, and inhibiting factors of the guidance and counseling for children in kindergarten Kemala Bhayangkari 13 Pontianak Kota. The method was descriptive method, with the form of qualitative research and case study approach to two children from class A and B4. Source of data derived from interview with the headmaster of the kindergarten, teachers and parents, observation result and documentary study. The results of this study described the form of planning which includes the identification of the learners’ problem through the child’s personal data form. Implementation included the data collection service, information, counseling, placement and evaluation and follow-up which had been completed properly. Evaluation included correspondence between the program and the implementation, adherence to the program, barriers, children’s, teachers’ and parents’ responses and the change in progress in giving guidance was also run as a whole. Inhibiting factors encountered were shortage of guidance personnel, inadequate facilities and infrastructures and undone supervision in kindergarten. Keywords: Guidance Services, Counseling Service and Early Childhood.